Peculiarities of Culture and In vitro Contact Interaction of Cryopreserved Thymic Multipotent Stromal Cells and Hemopoietic Cells - Nikolska, Kateryna I. (Problems of Cryobiology and Cryomedicine, 2018)
The cultural properties of cryopreserved and native thymic multipotent stromal cells (MSCs) of CBA mice were investigated. These cells differentiated in osteogenic and adipogenic directions in special media. Native and cryopreserved cells showed similar properties when cultured in glass petri dishes, plastic plates and cellophane. Both native and cryopreserved MSCs of thymus formed fibroblast colonies on glass and plastic surfaces. Cell growth was observed in cellophane. The thymus MSCs were found to have a membrane affinity for thymocytes, lymphocytes of lymph nodes and fetal liver cells. This determined their ability to interact with various hematopoietic cells with the formation of associations in the form of fibroblast-lymphocytic rosettes (FLR). The most effective, i.e. with the FLR formation, contact interaction was performed when the MSCs and thymocytes were involved, although the cells of mice lymph nodes and fetal liver also formed a significant number of FLRs. MSCs cryopreservation did no affect their ability to the contact interaction, that confirmed the possibility of using the cryopreservation to create appropriate cell transplants. Probl Cryobiol Cryomed 2018; 28(1): 005-013